Prevalence of herbal and traditional medicine in Ethiopia: a systematic review and meta-analysis of 20-year studies - Nigatu Tuasha; Sintayehu Fekadu; Serawit Deyno (Systematic Reviews, 2023)
Abstract Background The widely accepted prevalence of traditional medicine (TM) in Ethiopia was about 80 %, of which 95 % were sourced from plants. The purpose of this study was to update knowledge of the prevalence of herbal medicine or TM in Ethiopia and describe the characteristics of the population mostly relying on herbal medicine or TM to inform health policy-makers. Methods PubMed, Google Scholar, Hinari, Scopus, and the Directory of Open Access Journals (DOAJ) were searched. The methodological quality of each included study was assessed using the quality assessment checklist for prevalence studies. Meta-analysis was conducted using STATA version 17, and the heterogeneity between studies was assessed using I 2 test statistics based on the random effect model. Forest and funnel plots were used to present the data. Subgroup analysis was done by the study population, region, and setting. Results Thirty-six studies with a total of 16,288 participants met the inclusion criteria. Meta-analysis of the study revealed that the prevalence of herbal medicine use in Ethiopia is 46 % (95 % CI, 37–54 %), with significant heterogeneity among the studies (I 2 = 99.19 %). Egger’s test for publication bias of herbal medicine use revealed significant results (Egger, P = 0.002) which indicates possible missing of small sample size studies. The prevalence of TM use in Ethiopia is 65 % (95 % CI, 52–77 %) with significant heterogeneity among the studies (I 2 = 99.18 %). Egger’s test for publication bias of TM use revealed non-significant results (Egger, P = 0.275). The subgroup analysis by the study setting and the region revealed variability amongst the studies. Community-based studies and Oromia National Regional State showed higher prevalence. By population type, a higher prevalence of TM use was observed amongst children and lowest amongst malaria suspects. Conclusions The current study revealed that TM/herbal medicine utilization remained an important source of primary healthcare in Ethiopia. In comparison to the commonly reported prevalence of TM/herbal medicine, there is a considerable decline in TM/herbal medicine prevalence. High TM/herbal medicine use tendency during pregnancy necessitates safety studies to optimize the utilization.